Upregulation of the ferroptosis-related STEAP3 gene is a specific predictor of poor triple-negative breast cancer patient outcomes - Yuan, Lifang; Liu, Jiannan; Bao, Lei; Qu, Huajun; Xiang, Jinyu; Sun, Ping (Frontiers in Oncology, 2023)
This study was designed to assess ferroptosis regulator gene (FRG) expression patterns in patients with triple-negative breast cancer (TNBC) based on data derived from The Cancer Genome Atlas (TCGA). Further, it was utilized to establish a TNBC FRG signature, after which the association between this signature and the tumor immune microenvironment (TIME) composition was assessed, and relevant prognostic factors were explored.